2363. Clinician Educators within Infectious Diseases Society of America (IDSA): Who We Are, What We Do, and What We Need to Succeed. (15th December 2022) - Zimmer, Andrea J; Barsoumian, Alice E; Hsu, Jennifer; Walker, Jeremey; Summers, Nathan A; Derber, Catherine; Allen, Bradley L; Ressner, Roseanne; Kershaw, Colleen; Luther, Vera
Abstract: Background: To best support, its membership, the IDSA Medical Education Community of Practice (Med Ed CoP) must know the spectrum of educational duties, common challenges, and needs among its clinician educators (CE). Further, benchmark data for medical education is lacking, including average time to perform duties, salary support, and other resources. Therefore, we conducted a survey to help identify opportunities for institutions and IDSA to support Infectious Disease (ID) CE. Methods: We conducted an anonymous electronic mixed-methods survey of ID CE faculty in the United States. The survey link was distributed through the IDSA Med Ed CoP and Program Director discussion forums and receptions at IDWeek 2021. Results: Approximately 90/552 (16%) participants completed a majority of the survey. Respondents were evenly distributed by gender and geographic region. A majority of respondents were Caucasian, aged 30 – 49 years, and at the Assistant or Associate Professor level (Table 1). Overall breakdown of allocated duties is as follows; median education full-time equivalent (FTE) was 0.25, clinical FTE=0.50, administrative FTE=0.16, and research FTE=0 (Table 1). Faculty most commonly taught medical students (95%), physician residents (92%), and fellows (88%) and held positions within ID fellowship programs (69%) and medical schools (50%, Table 2). CE's common challenges included competing responsibilities (69%), lack of medical education mentorship (51%), and inexperience in medical education publication (67%). In addition, 77% reported burnout in the past year, frequently due to an increased pandemic-related workload. CEs would like to see opportunities for IDSA grants, advocacy for salary support, and increased opportunities to publish within IDSA journals. CEs report finding reward in their educational work related to: teaching the next generation, developing relationships with learners and colleagues, and promoting others' success. Conclusion: In our study, ID CEs identified common challenges including educational work often requiring more time than allocated FTE, lack of mentors, publishing educational activities, recognition of CE work for promotion, and burnout. Additionally, ID CEs identified practical strategies in which their institutions and IDSA can offer support. Disclosures: All Authors : No reported disclosures.